2014
DOI: 10.1371/journal.pbio.1001968
|View full text |Cite
|
Sign up to set email alerts
|

The Chromatin Assembly Factor 1 Promotes Rad51-Dependent Template Switches at Replication Forks by Counteracting D-Loop Disassembly by the RecQ-Type Helicase Rqh1

Abstract: A molecular switch for times of replication stress - Chromatin Assembly Factor 1 helps to protect DNA during recombination-mediated template-switching, favoring the rescue of stalled replication forks by both beneficial and detrimental homologous recombination events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
50
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(56 citation statements)
references
References 68 publications
6
50
0
Order By: Relevance
“…Hoek et al postulated that KU70/80 recruits CAF-1 to DNA damage repair sites independently of PCNA because there is a need for new nucleosome assembly without a need for large-scale DNA synthesis [37]. Furthermore, Werner syndrome protein (WRN), a RecQ family DNA helicase, has recently been shown to recruit CHAF1a to sites of DNA damage through direct interactions mediated by its helicase and RQC domains: this complex is promotes DNA repair through homologous recombination [39, 40]. …”
Section: The Chaf1a Subunitmentioning
confidence: 99%
“…Hoek et al postulated that KU70/80 recruits CAF-1 to DNA damage repair sites independently of PCNA because there is a need for new nucleosome assembly without a need for large-scale DNA synthesis [37]. Furthermore, Werner syndrome protein (WRN), a RecQ family DNA helicase, has recently been shown to recruit CHAF1a to sites of DNA damage through direct interactions mediated by its helicase and RQC domains: this complex is promotes DNA repair through homologous recombination [39, 40]. …”
Section: The Chaf1a Subunitmentioning
confidence: 99%
“…Rationale for the experiments performed in this study. CAF-1 was shown to stabilize Dloops in S. pombe that occur as the result of template switching at replication forks (Pietrobon et al 2014). This observation encouraged us to test if the histone chaperones CAF-1 and Rtt106 play roles in stabilizing recombination intermediates during HR, and in turn suppressing rejection.…”
Section: Resultsmentioning
confidence: 97%
“…in S. pombe and BLM and WRN in humans) physically interact with the large subunit of CAF-1 (Pietrobon et al 2014;Jiao et al 2004;Jiao et al 2007). Additionally, Pietrobon et al (2014) showed that CAF-1 suppresses D-loop disassembly by Rqh1 during template switching. Based on these observations, it is possible that CAF-1 physically interacts with Sgs1 in budding yeast and counteracts its unwinding activity during heteroduplex rejection.…”
Section: Various Studies Have Shown In Fission Yeast and Humans That mentioning
confidence: 99%
See 2 more Smart Citations